Analysis of Macroeconomic Variables Affecting Inflation and Exchange Rates - Vietha Devia Sagita Sumantri; Faishal Fadli (Fakultas Ekonomi, Universitas Bangka Belitung, 2022)
This study aims to examine the movement of macroeconomic variables, especially inflation and exchange rates. Inflation affects the exchange rate through the Law of One Price and Purchasing Power Parity, while the exchange rate affects inflation through the Exchange Rate Pass-Through Effect. This study also aims to examine the effect of other macroeconomic factors on inflation and exchange rates. The variables studied and suspected of influencing inflation are interest rates, money supply, exports, imports, government spending, unemployment, and exchange rates. While the variables studied and suspected of influencing the exchange rate are the difference in interest rates between domestic and foreign interest rates, trade balance, public debt, inflation and exchange rates MYR/USD, THB/USD, PHP/USD, SGD/USD. The research period is from 2004-2017. The research method used is the Two-Staged Least Square model. The results found that there was no simultaneity between inflation and the exchange rate after adding the control variable. Significant factors that partially affect inflation are exports, imports, government spending, unemployment, and the rupiah exchange rate. Meanwhile, interest rates and money supply partially have no significant effect. In terms of the IDR exchange rate, significant factors that partially affect IDR are the difference in interest rates between Indonesia and the US, government debt, trade balance, MYR, THB, and SGD. Meanwhile, PHP and inflation have no significant effect on the IDR.